Live attenuated influenza vaccines are not effective: new data from the US - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
An analysis of data from vaccinations for 2015-16 influenza season has demonstrated complete uselessness of the live attenuated vaccines.